Cardiovascular Adaptations to Resistance Training in Elderly Postmenopausal Women - Gerage, A. M.; Forjaz, C.L. M.; Nascimento, M. A.; Januário, R.S. B.; Polito, M. D.; Cyrino, E. S. (International Journal of Sports Medicine, 2013)
The purpose of this study was to investigate the effect of resistance training on resting blood pressure and heart rate variability in elderly postmenopausal women. 29 untrained, non-hypertensive elderly women were randomly assigned to 2 groups: an intervention group (n=15, 65.5±5.0 years, 57.3±6.5 kg, 156.7±5.1 cm) that underwent a supervised resistance training program (8 exercises, 2 sets, 10–15 repetitions, 3 times/week) or a control group (n=14, 66.2±4.1 years, 61.1±11.7 kg, 157.5±7.1 cm) that participated in a supervised stretching program (25–30 min/session, 2 times/week). Resting auscultatory blood pressure, heart rate variability, evaluated from short recordings in a seated position, and maximal dynamic strength (1-RM test) were measured at baseline and after 12 weeks. A group x time ANOVA revealed that muscular strength increased significantly in the resistance training group (+ 10.2% for bench press and +12.7% for leg extension, P<0.05). Systolic blood pressure was reduced significantly in the resistance training group from pre- to post-intervention period (− 5 mmHg; P<0.05), while no significant effect was noted for diastolic blood pressure and heart rate variability indexes (P>0.05). None of these variables changed in the control group throughout the study. In conclusion, a supervised resistance training program improved muscular strength and reduced systolic blood pressure without affecting diastolic blood pressure and heart rate variability in elderly postmenopausal women.
Keywords: muscular strength; blood pressure; heart rate variability; aging